Simulation in teaching high-alert medication administration for nurses: a brief overview (Research, Society and Development, 2021)
The objective was to design a brief overview of the use of realistic simulation in teaching the safe administration of high risk medicine (HRMs) during nursing education. Studies have reported low knowledge about the safe use of HRMs in nursing students and nurses. In support of this knowledge, the realization of realistic simulation during academic training has the potential to provide the development of safety as well as the theoretical-practical articulation related to acting in real clinical scenarios found in different contexts of nursing practice. The consolidation of patient safety principles and concepts is notorious, especially involving the teaching of HRMs administration during nursing education. Realistic simulation can be understood as an innovative active teaching methodology and can contribute to reducing medication errors and, consequently, promoting safer patient care.